An Analysis of a Specimen of Silver-Gray or Glazy Iron - Edward Hart (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1877)
THE specimen of glazy iron used for analysis was highly characteristic in appearance. It was made at one of the furnaces of the Glendon Iron Works, working a light burden of ore with a highly silicious cinder. There are very few records of analyses of this variety of iron. I have been able to find but the two given by Bell, and I add these to my analysis for comparison.